Measuring iron concentration in the blood samples of some autistic children from Baghdad City: Exploring Potential Nutritional Links to Autism: A Study of Iron in Baghdad Children - sulaiman, Ezzuldin; Hind Suhail Abdulhay (ASJ - Academic Science Journal, 2025)
Autism spectrum disorder (ASD) research delved into the correlation between genetic susceptibility and various environmental factors, including diet, drug exposure, and environmental toxicants such as exposure to heavy metals. Iron is one of the heavy metals around which there is much controversy regarding their role as neurotoxins in the development of autism, its excess in the brain may cause Alzheimer’s disease or Parkinson’s disease, while iron deficiency in the blood may increase levels of other heavy metals in the blood and brain, such as cadmium and lead. This study aimed to measure iron levels in samples of autistic children in Baghdad City. Blood serum samples were collected from 60 patients with autism spectrum disorder and 35 healthy controls to measure iron levels. The samples were frozen and analyzed using flame atomic absorption spectrometry. The study found that children with autism had significantly higher iron levels than healthy children with a mean value of 37.409±5.969 μg/ d (P ≤ 0.01). Possible causes for this condition include specific drugs, genetic disorders, or the dietary habits of the ASD. Iron may be a factor in ASD, and it’s possible that Iraqi environmental pollution is the cause of the higher iron levels in autistic children. The study suggests that any change in iron levels might have an impact on the brain since it is an important component of the body. Without a doubt, toxic metal overload or key element shortages can cause epigenetic modifications that impair neuronal maturation and lead to neurodevelopmental abnormalities in the form of developmental disorders in children.